Prospective Evaluation of the Safety and Efficacy of THRIVE for Children Undergoing Airway Evaluation. Issue 5 (September 2020) - Okland, Tyler S.; Liu, George S.; Caruso, Thomas J.; Sidell, Douglas R.
Abstract : Background: Transnasal Humidified Rapid-Insufflation Ventilatory Exchange (THRIVE) is a humidified high-flow nasal cannula capable of extending apneic time. Although THRIVE is assumed to stent upper airway soft tissues, this has not been objectively evaluated. Also, there are no prior studies providing safety and efficacy data for those patients undergoing upper airway evaluation using THRIVE. Methods: This report is a prospective study of the safety and efficacy of THRIVE in pediatric patients younger than 18 years old undergoing drug-induced sleep endoscopy. We positioned a flexible laryngoscope to view the larynx, and photographs were taken with no THRIVE flow (control) and with THRIVE flow at 10 and 20 liters per minute (LPM). Upper airway patency was measured using epiglottis to posterior pharynx distance, laryngeal inlet area, and modified Cormack–Lehane score at the trialed parameters. Vomiting and aspiration were our primary safety endpoints. Results: Eleven patients (6 women) with a mean age of 5.3 ± 2.1 years (2–8 years; SD, 2.05) were enrolled. Measurements of upper airway patency showed a significant THRIVE flow–associated increase in epiglottis to posterior pharynx distance (105 ± 54 at 10 L/min and 199 ± 67 at 20 L/min; P = 0.007) and nonsignificant increase of laryngeal inlet area (206 ± 148 at 10 L/min and 361 ± 190 at 20 L/min; P = 0.07). Cormack–Lehane score improved significantly at higher THRIVE volumes ( P = 0.006). Conclusions: THRIVE appears to safely improve upper airway patency during sleep endoscopy in the pediatric patient. In this study, we objectively document the flow-dependent increase in laryngeal patency associated with THRIVE.